Perintah Membaca dalam Al-Qur’an Perspektif Pendidikan (Surah Al-Alaq) - Dirwan Dirwan; Bunyamin Bunyamin; St Umrah (IAIN Sorong, 2028)
Reading is a commandment from Allah. commanded through al-Qur'an Surah al-Alaq verse 1 which was revealed through the intermediary angel Gabriel to the Prophet Muhammad. Which will be preached to all the human Ummah specifically to the Ummah who always follows the teachings of Islam. Therefore, we must read the Koran, both reading directly (written) and reading with signs of Allah's power. (implied). Which has a variety of discussions ranging from reading the Koran, mentadabburi, practice and practice so as to create a generation of Qur'ani. In this paper using library research with the method of using library data collection techniques (Library Research) that uses various kinds of existing literature such as books, books of hadith, books of interpretation and the Qur'an that will help in using methods, deductive, inductive and comparative. And it was concluded that the command to read in the Koran so that it can be seen that reading is not just a job, not a mere hobby but as a very important command that will underlie all our activities in this world, let alone a prosecutor of knowledge, reading also is a foundation to go to the path that is blessed by Allah.